(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2019)
SKIB-71, the acronym of Sashi, Krishna, Indra and Batsa represents a very significant phase in the movement of modern Nepali paintings. These four artists launched a movement in paintings a quarter of a century ago with a view to inspiring young artists and opening new vista of communications with artists using other media and methods. Their personal involvements in art activities couples with their experimentations created a unique atmosphere in Nepali paintings characterised by such features as the gatherings of artists, interactions, exhibitions and, above all the pedagogy of arts. After the sad demise of Indra Pradhan in 1994, three of them continued to work for which they chose to engage in art pedagogy or to work quietly on cultural motifs. Among the many reasons to consider them as part of art activities today is their impact on art education, accentuation of the subject of experimentation and participation in the art activities of present times.